Intrusion Detection Systems. Model and implementation of a knowledge base of intrusions into the computer system - Barczak, Andrzej; Tokajuk, Grzegorz (Studia Informatica. System and information technology, 2019)
There are many complementary approaches to detecting intrusions e.g. be-havior based approach, knowledge-based (KB) approach. The paper described the last one. The essential problems of determination of a KB for intrusion detection systems (IDS), prepared of threat signature, architecture of database containing the rules are considered.